The negative impacts of bisphenols on thyroid function in adults with bisphenol A exposure level exceeding the tolerable daily intake - Ziwei Pei; Lei Zhang; Yan Bao; Jingguang Li; Qin Zhuo (Ecotoxicology and Environmental Safety)
In 2023, European Food Safety Authority (EFSA) published a re-evaluation of the safety of bisphenol A (BPA), establishing the new tolerable daily intake (TDI) as 0.2 ng/kg·bw/day with a 20,000-fold reduction compared to 2015, which regained public concern about the impact of bisphenols (BPs) on human health. In order to explore the health risk to thyroid function of BPs, in this study, we assessed the internal exposure levels of BPs and the relationships between urinary BPs and thyroid function in general adults. We carried out a cross-sectional study in Chengdu, China, recruiting 1486 adults without special indentities and diseases (aged 18–68), and measured 6 BPs in urine. We found BPA was the predominant compound in urinary samples of this population, and the estimated daily intake (EDI) of BPA was 0.027 μg/kg·bw/day (geometric mean), exceeding the TDI value by two orders of magnitude. Using multivariable regression model, we observed a negative association between BPA and T3 and T3/T4 in males. Trend tests indicated that higher BPA levels were correlated with higher rates of subclinical hypothyroidism (SCH) in males (OR=1.383, 95 % CI [1.024, 1.867]). We also observed that bisphenol F (BPF) contributed to the occurrence of thyroid globulin antibody positivity (TGAb.P) in both males and females. Although the use of BPs has been restricted, the adverse health effects still deserve public attention.